Molecular characterization of genes encoding leucoanthocyanidin reductase involved in proanthocyanidin biosynthesis in apple - Liao, Liao; Vimolmangkang, Sornkanok; Wei, Guochao; Zhou, Hui; Korban, Schuyler S.; Han, Yuepeng (Frontiers in Plant Science, 2015)
Proanthocyanidins (PAs) are the major component of phenolics in apple, but mechanisms involved in PA biosynthesis remain unclear. Here, the relationship between the PA biosynthesis and the expression of genes encoding leucoanthocyanidin reductase (LAR) and anthocyanidin reductase (ANR) was investigated in fruit skin of one apple cultivar and three crabapples. Transcript levels of LAR1 and ANR2 genes were significantly correlated with the contents of catechin and epicatechin, respectively, which suggests their active roles in PA synthesis. Surprisingly, transcript levels for both LAR1 and LAR2 genes were almost undetectable in two crabapples that accumulated both flavan-3-ols and PAs. This contradicts the previous finding that LAR1 gene is a strong candidate regulating the accumulation of metabolites such as epicatechin and PAs in apple. Ectopic expression of apple MdLAR1 gene in tobacco suppresses expression of the late genes in anthocyanin biosynthetic pathway, resulting in loss of anthocyanin in flowers. Interestingly, a decrease in PA biosynthesis was also observed in flowers of transgenic tobacco plants overexpressing the MdLAR1 gene, which could be attributed to decreased expression of both the NtANR1 and NtANR2 genes. Our study not only confirms the in vivo function of apple LAR1 gene, but it is also helpful for understanding the mechanism of PA biosynthesis.